Pre-diagnosis thyroid hormone dysfunction is associated with cancer mortality. Issue 11 (20th September 2021) - Krashin, Eilon; Silverman, Barbara; Steinberg, David M; Yekutieli, Daniel; Giveon, Shmuel; Fabian, Offer; Hercbergs, Aleck; Davis, Paul J; Ellis, Martin; Ashur-Fabian, Osnat
Abstract : Research on the association between thyroid hormone levels and cancer mortality remains limited and inconclusive. We determined the relation of thyroid stimulating hormone (TSH), free T4 (FT4), and free T3 (FT3) levels with mortality in overall cancer and specific tumor types. Thyroid hormone levels 1–5 years prior to cancer diagnosis, as well as multiple clinical and demographic parameters, were retrospectively collected for 10, 325 Israeli cancer patients, diagnosed between 2000 and 2016. Patients treated with thyroid altering medications were excluded. Cancer diagnosis was determined via the Israel National Cancer Registry. Multivariate-adjusted Cox proportional hazards model was used to assess the hazard ratios (HRs) based on thyroid hormone function for cancer mortality. A total of 5265 patients died during the follow-up period (median of 4.4 years). TSH, FT4, and FT3 levels in the hypothyroid range were associated with increase in overall mortality (adjusted HR 1.20, 1.74, 1.87, respectively). We further analyzed the association between TSH and mortality in 14 cancer subgroups. Specifically, TSH in both the hyperthyroid and hypothyroid range was associated with melanoma mortality (adjusted HR 2.20, 4.47, respectively). In conclusion, pre-diagnosis of thyroid dysfunction is associated with increased cancer mortality, a relation likely driven by specific cancer types. These findings suggest that thyroid hormones may potentially serve as prognostic markers in cancer.